2016
DOI: 10.1038/srep23117
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-634 suppresses survival and matrix synthesis of human osteoarthritis chondrocytes by targeting PIK3R1

Abstract: Osteoarthritis (OA) is a degenerative disease characterized by deterioration of articular cartilage. Recent studies have demonstrated the importance of some microRNAs in cartilage damage. The aim of this study was to identify and characterize the expression of microRNA-634 (miR-634) in normal and OA chondrocytes, and to determine its role in OA pathogenesis. Human normal and OA chondrocytes obtained from patients were cultured in vitro. Transfection with miR-634 mimic or inhibitor was employed to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…OA is characterized by deterioration of functions of chondrocytes, an integral part of articular cartilage, subchondral bone and joint margins [1]. Studies have shown that proteolytic enzymes such as matrix metalloproteinases (MMP), secreted by chondrocytes are involved in degradation of cartilage [2, 3]. The pathogenesis of OA is a multifactorial disorder with genetic, developmental, biochemical and biomechanical factors contributing to the development of disease process [1, 3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OA is characterized by deterioration of functions of chondrocytes, an integral part of articular cartilage, subchondral bone and joint margins [1]. Studies have shown that proteolytic enzymes such as matrix metalloproteinases (MMP), secreted by chondrocytes are involved in degradation of cartilage [2, 3]. The pathogenesis of OA is a multifactorial disorder with genetic, developmental, biochemical and biomechanical factors contributing to the development of disease process [1, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is one of the commonest chronic degenerative diseases, especially among the old age people, seriously affects the quality of life of the affected patients [1, 2]. OA is characterized by deterioration of functions of chondrocytes, an integral part of articular cartilage, subchondral bone and joint margins [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies demonstrated their importance in maintaining cartilage homeostasis and their effects on promoting the pathogenesis of OA. For instance, it was claimed in 2016 by Xu Cui and his group that by targeting PIK3R1, overexpression of miR-634 can suppress survival and matrix synthesis of human osteoarthritis chondrocytes (2). It is illustrated by Tadahiro Sakai and his colleagues that miR125b plays a pivotal role in regulating expression of aggrecanase-1 (ADAMTS-4) in human osteoarthritic chondrocytes (3).…”
Section: Introductionmentioning
confidence: 99%
“…The reason of the discrepancies between mRNA and protein expression in our study might be due to the posttranscriptional regulation of the mRNA which has been reported previously12. For instance, microRNAs were known to regulate the target mRNA translation either through translational silencing of the mRNA or degradation of the mRNA in osteoarthritis and chondrogenesis1314. It should be noted that there was a tendency of increased COL 2 production of both MSCs with time, thus it is reasonable to expect the same even higher level of COL 2 of MSCs groups compared to that of ACCs with longer culturing time or in vivo transplantation.…”
Section: Discussionmentioning
confidence: 58%